Views from the margins : creating identities in modern France - Callahan, Kevin J.; Curtis, Sarah Ann (University of Nebraska Press, 2008)
This collection of essays offers examples drawn from an imperial history of France that show the power of the periphery to shape diverse and dynamic modern French identities at its center. Each essay explains French identity as a fluid process rather than a category into which French citizens (and immigrants) are expected to fit. In using a core/periphery framework to explore identity creation, Views from the Margins breaks new ground in bringing together diverse historical topics from politics, religion, regionalism, consumerism, nationalism, and gendered aspects of civic and legal engagement.